Health-related quality-of-life outcomes in patients with advanced renal cell carcinoma treated with lenvatinib plus pembrolizumab or everolimus versus sunitinib (CLEAR): a randomised, phase 3 study. Issue 6 (June 2022) - Motzer, Robert; Porta, Camillo; Alekseev, Boris; Rha, Sun Young; Choueiri, Toni K; Mendez-Vidal, Maria Jose; Hong, Sung-Hoo; Kapoor, Anil; Goh, Jeffrey C; Eto, Masatoshi; Bennett, Lee; Wang, Jinyi; et al.
Summary: Background: Results from the phase 3 CLEAR study showed that lenvatinib plus pembrolizumab improved progression-free survival and overall survival compared with sunitinib in patients with advanced renal cell carcinoma. We aimed to assess the health-related quality-of-life (HRQOL) outcomes from the CLEAR study. Methods: This open-label, randomised, phase 3 study was done across 200 hospitals and cancer centres in 20 countries. Patients were required to be 18 years or older, with advanced clear-cell renal cell carcinoma, and a Karnofsky performance status of 70% or higher. Patients who had received previous systemic anticancer therapy for renal cell carcinoma were not eligible. Patients were randomly assigned (1:1:1) to lenvatinib (oral 20 mg per day) plus pembrolizumab (intravenous 200 mg every 21 days), lenvatinib (oral 18 mg per day) plus everolimus (oral 5 mg per day) in 21-day cycles, or sunitinib (oral 50 mg per day, 4 weeks on followed by 2 weeks off). Patients were assigned to treatments with a computer-generated randomisation scheme and were stratified by geographical region and Memorial Sloan Kettering Cancer Center prognostic groups. The primary endpoint, previously reported, was progression-free survival, and HRQOL was a secondary endpoint. Most HRQOL analyses were done in patients who underwent randomisation, received at least one dose of study treatment, and had any HRQOL data. Completion and compliance analyses were done in the full analysis set. Functional Assessment of Cancer Therapy Kidney Symptom Index-Disease-Related Symptoms (FKSI-DRS), European Organisation for the Research and Treatment of Cancer Quality of Life Questionnaire-Core 30 (EORTC QLQ-C30), and the EQ-5D-3 Level (EQ-5D-3L) preference questionnaire were administered at baseline and on day 1 of each subsequent 21-day cycle. This study is registered with ClinicalTrials.gov, NCT02811861, and is closed to new participants. Findings: Between Oct 13, 2016, and July 24, 2019, 355 patients were randomly assigned to the lenvatinib plus pembrolizumab group, 357 to the lenvatinib plus everolimus group, and 357 to the sunitinib group. Median follow-up for HRQOL analyses was 12·9 months (IQR 5·6–22·3). Because of the promising efficacy and safety results of lenvatinib plus pembrolizumab in the first-line setting, we focus the HRQOL results in this report on that combination versus sunitinib. Mean change from baseline in the lenvatinib plus pembrolizumab group compared with the sunitinib group was –1·75 (SE 0·59) versus –2·19 (0·66) for FKSI-DRS, –5·93 (0·86) versus –6·73 (0·94) for EORTC QLQ-C30 global health status/quality of life (GHS/QOL), and –4·96 (0·85) versus –6·64 (0·94) for the EQ-5D visual analogue scale (VAS). Median time to first deterioration in the lenvatinib plus pembrolizumab group compared with the sunitinib group was 9·14 weeks (95% CI 6·43–12·14) versus 12·14 weeks (9·14–15·29; HR 1·13 [95% CI 0·94–1·35], log-rank p=0·20) for FKSI-DRS, 12·00 weeks (7·29–15·14) versus 9·14 weeks (6·29–12·14; 0·88 [0·74–1·05], log-rank p=0·17) for EORTC QLQ-C30 GHS/QOL, and 9·43 weeks (6·43–12·29) versus 9·14 weeks (6·29–12·00; 0·83 [0·70–0·99], log-rank p=0·041) for the EQ-5D VAS. Median time to definitive deterioration in the lenvatinib plus pembrolizumab group compared with the sunitinib group was 134·14 weeks (95% CI 120·00–not estimable) versus 117·43 weeks (90·14–131·29; HR 0·70 [95% CI 0·53–0·92], log-rank p=0·0081) for FKSI-DRS, 114·29 weeks (102·14–153·29) versus 75·14 weeks (57·29–105·14; 0·60 [0·47–0·77], log-rank p<0·0001) for EORTC QLQ-C30 GHS/QOL, and 124·86 weeks (94·71–134·57) versus 74·86 weeks (54·14–96·00; 0·67 [0·53–0·85], log-rank p=0·0012) for the EQ-5D VAS. No outcomes on any of the instruments significantly favoured sunitinib over lenvatinib plus pembrolizumab. Most HRQOL comparisons of lenvatinib plus everolimus versus sunitinib were similar or favoured sunitinib. Interpretation: These HRQOL results demonstrate that patients given lenvatinib plus pembrolizumab treatment had similar or favourable scores compared with patients given sunitinib, particularly with respect to time to definitive deterioration. These results support the efficacy and safety profile of lenvatinib plus pembrolizumab as first-line therapy for patients with advanced renal cell carcinoma. Funding: Eisai (Nutley, NJ, USA) and Merck Sharp & Dohme, a subsidiary of Merck & Co (Kenilworth, NJ, USA).